2002
DOI: 10.1038/sj.ijo.0802213
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and target organ damage: the kidney

Abstract: Obesity is a risk marker for progressive renal function loss in patients with known renal disease. There is, however, increasing evidence that obesity may also damage the kidney in otherwise healthy subjects. There appears to be an intriguing parallel between the renal effects of obesity and those of diabetes. First, an increased renal blood flow and glomerular filtration rate has been described in obesity and, second, microalbuminuria is found to be related to obesity. These two events are known to predict fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
122
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(133 citation statements)
references
References 21 publications
5
122
2
4
Order By: Relevance
“…Previous studies have shown that obesity is associated with MA. 22,[27][28][29] However, in our study, WC and abdominal obesity had a significant association with MA whereas BMI had not. Similarly, several studies have suggested a differential effect according to body morphology.…”
Section: Discussioncontrasting
confidence: 70%
“…Previous studies have shown that obesity is associated with MA. 22,[27][28][29] However, in our study, WC and abdominal obesity had a significant association with MA whereas BMI had not. Similarly, several studies have suggested a differential effect according to body morphology.…”
Section: Discussioncontrasting
confidence: 70%
“…Indeed, the frequency of microalbuminuria in the general population has been shown to increase with the degree of obesity. 29 Its frequency was significantly higher in subjects with MS than in those without MS suggesting that in children, as in adults, 30 microalbuminuria is associated with MS. Obese children with MS also had higher concentrations of PAI-1 and uric acid which together with microalbuminuria explained 10.6% of the variance of the MS. This proportion is similar to the 7.4% of the total variance of MS explained by an 'inflammatory factor' in nondiabetic individuals participating in the Insulin Resistance Atherosclerosis Study.…”
Section: Discussionmentioning
confidence: 93%
“…20,41 Obesity, itself, contributes to the development and progression of CKD, independent of elevated BP or diabetes. 42 The risk for end-stage renal disease is progressively higher at increasing BMI levels and in extremely obese individuals in which such risk is much higher than that in persons with normal BMI. 41 Elevated sympathetic nervous activity has been observed in patients with CKD, regardless of obesity, hypertension or diabetes.…”
Section: Discussionmentioning
confidence: 99%